2019
DOI: 10.1002/joc.6128
|View full text |Cite
|
Sign up to set email alerts
|

US temperatures: Time trends and persistence

Abstract: This paper investigates the time trend coefficients in the temperatures in 48 US states using monthly data from January 1895 to December 2017, as well as in their anomalies with respect to the base period 1901–2000. For this purpose, we use techniques based on fractional integration, which is a more general approach than the standard methods used in the literature based on integer differentiation. The results indicate that with the exception of 10 states, in the remaining 38, the temperature anomalies have inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 90 publications
(123 reference statements)
2
8
0
Order By: Relevance
“…Long memory is a feature in time series data that means that observations are highly dependent even if they are far apart in time. Within this category, widely observed in climatological data (Yuan et al, 2014;Jiang et al, 2015;Gil-Alana and Sauci, 2019), a well-known parametric model is the one based on fractional integration that means that the number of differences required in a series to render it stationary I(0) is a fractional value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long memory is a feature in time series data that means that observations are highly dependent even if they are far apart in time. Within this category, widely observed in climatological data (Yuan et al, 2014;Jiang et al, 2015;Gil-Alana and Sauci, 2019), a well-known parametric model is the one based on fractional integration that means that the number of differences required in a series to render it stationary I(0) is a fractional value.…”
Section: Methodsmentioning
confidence: 99%
“…A large part of the most recent research is now studying the evolution of temperatures taking into account the long-memory property of the series, both at a global scale, Gil-Alana (2005), dealing with Northern Hemisphere temperatures, and at a local scale, such as Franzke (2010), who explored eight stations in Antarctica, observing longrange memory behavior Jiang et al (2015). also observed long-memory in the air temperatures in 552 Chinese stations;Massah and Kantz (2016) andYuan et al (2014Yuan et al ( , 2015 used detrended fluctuation analysis (DFA) to detect long-memory behavior of temperature series in Europe and in Antarctica respectively Gil-Alana and Sauci (2019).…”
mentioning
confidence: 99%
“…Such tests are widely used in many disciplines, including climatology (Gil-Alana, 2005;Gil-Alana, 2008;Gil-Alana and Sauci, 2019), economics (Gil-Alana and Robinson, 1997), finance (Gil-Alana and Moreno, 2012; Abbritti et al, 2016), and environmental sciences (Solarin and Bello, 2018;Gil-Alana and Trani, 2019).…”
Section: Robinson Tests For Fractional Differentiationmentioning
confidence: 99%
“…Arora et al [59] reported 100-year temperature increase values of 0.92 and 0.09 °C in the maximum and minimum temperatures, respectively, over India. Gil-Alana and Sauci [60] indicated that the highest increase in air temperature was about 2.9 °C over the last 100 years observed at New Jersey and Rhode Island in the United States. Positive trend in air temperature was reported in Bangladesh during the 1961-2008 period [61].…”
Section: Trend Analysis In Annual Maximum and Minimum Temperaturesmentioning
confidence: 99%